ANALISIS PENGARUH LITERASI AKAD SYARIAH ANGGOTA KOPERASI TERHADAP PENGAMBILAN KEPUTUSAN PEMBIAYAAN DI KOPERASI SIMPAN PINJAM DAN PEMBIAYAAN SYARIAH BAYTUL IKHTIAR CABANG PAMIJAHAN, KABUPATEN BOGOR, JAWA BARAT - Fadilah, Muhamad Ichsan; Thantawi, Tubagus Rifqy; Mubarok, Mohamad Kharis (SAHID BANKING JOURNAL, 2024)
Today's Islamic financial institutions show very rapid progress in all countries that have a Muslim majority and with the development of knowledge and awareness about the prohibitions that have been determined by Islamic sharia. Likewise in Indonesia, which has a majority Muslim population. The purpose on this study is to analyze and explain the influence of Sharia contract literacy which is divided into four factors that are considered to have an influence, namely the knowledge, abilities, attitudes and beliefs of members of KSPPS Baytul Ikhtiar Pamijahan Branch in making decisions to finance at KSPPS Baytul Ikhtiar. The method used on this research is quantitative method with the data collection method using primary data obtained through a questionnaire with a sample of 100 respondents